2013
DOI: 10.13045/acupunct.2013033
|View full text |Cite
|
Sign up to set email alerts
|

Case Study of with ( ) & ( ) Therapy Combined with Korean Medicine Treatment of Herniated Lumbar Intervertebral Disc Patients

Abstract: We divided into two groups. The group A(n=80) was treated with Gwanchim therapy combined with Korean medicine treatment, and the group B(n=23) was treated only Korean medicine treatment. We evaluated the treatment effect with the verbal numerical rating scale(VNRS), and compared admission day and one day after admission. Results : 1. In both two groups VNRS was decreased and this therapy is safety. 2. In group A, VNRS was decreased 10 to 5.68 and in group B, VNRS was decreased 10 to 8.7 Conclusion : This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
0
3
0
2
Order By: Relevance
“…In case reports that accompanied large dose pharmacopuncture [13], bee venom [14], and chuna [15] with Korean Medicine treatment, radiological change of the herniated disc was observed. Acupotomy has been shown to decrease pain [3][4][5], but to date there has not been a Korean clinical case reported that has compared radiological evidence of change before and after acupotomy using CT or MRI imaging. This study showed radiological change in the improvement of herniated disc symptoms in addition to NRS scores of pain severity, which decreased for both patients (cervical and lumbar HNP), when acupotomy and combined Korean Medicine treatment was performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case reports that accompanied large dose pharmacopuncture [13], bee venom [14], and chuna [15] with Korean Medicine treatment, radiological change of the herniated disc was observed. Acupotomy has been shown to decrease pain [3][4][5], but to date there has not been a Korean clinical case reported that has compared radiological evidence of change before and after acupotomy using CT or MRI imaging. This study showed radiological change in the improvement of herniated disc symptoms in addition to NRS scores of pain severity, which decreased for both patients (cervical and lumbar HNP), when acupotomy and combined Korean Medicine treatment was performed.…”
Section: Discussionmentioning
confidence: 99%
“…The aim is recovery of function to a normal active state by detaching the adhesion and nodes, of the damaged soft tissue [2]. In the last decade, numerous clinical trials have been conducted looking at the effectiveness of conservative Korean Medicine treatment on cervical and lumbar HNP, where acupotomy interventions have resulted in improvements [3][4][5]. However, few studies in Korea have reported follow-up radiological changes (CT or MRI) after acupotomy.…”
Section: Introductionmentioning
confidence: 99%
“…서 론 요추간판탈출증은 퇴행성 변화 또는 급격한 외압에 의해 섬유륜의 팽윤이나 파열로 수핵의 일부 또는 전부가 척수 강에 돌출되어 척수의 경막이나 신경근을 압박하여 요통 및 신경 증상을 유발하는 질환이다 1) . 수핵의 탈출로 신경 근이 압박 받으면 초기에는 미세혈관의 혈행장애, 부종, 화 학적 자극, 염증, 신경의 유합 및 자가면역 반응 등이 일어 나 통증이 발생한다 2) .…”
Section: Dochim;unclassified
“…요추 추간판 탈출증의 치료는 수술적 요법과 비수술적 요법으로 나눌 수 있는데 7) , 여러 보고에 의하면 수술의 절 대 적응증이나 마미 증후군 등으로 수술을 하는 경우는 1~3 %에 불과하며 8) , Kraemer 9) 는 추간판 탈출증으로 인 한 통증은 3주 정도에 개선되기 시작하고, 1년 안에 99 % 가 경감된다고 하여 수술적 치료가 불필요하다고 하였다. Saal et al 10,11) , Cavallier et al 12) , Maigne et al 13) , Bush et al 14) 의 보고에 따르면 탈출된 추간판은 수술 없이 보존 적 치료만으로 소실되는 것으로 나타났다.…”
Section: ⅰ 서 론unclassified